Dynamics of interleukin-6 in early period in the early period after simulation skeletal, cranial and combined injuries - Levchuk, R.; Gudyma, A.; Dzetsiukh, T. (Journal of Education, Health and Sport, 2015)
Levchuk R., Gudyma A., Dzetsiukh T. Dynamics of interleukin-6 in early period in the early period after simulation skeletal, cranial and combined injuries. Journal of Education, Health and Sport. 2015;5(9):694-699. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32195 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A694-699 https://pbn.nauka.gov.pl/works/657592 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. UDK 612.017–02:616.71–001.3/6]-092.9 DYNAMICS OF INTERLEUKIN-6 IN EARLY PERIOD IN THE EARLY PERIOD AFTER SIMULATION SKELETAL, CRANIAL AND COMBINED INJURIES R. Levchuk, A. Gudyma, T. Dzetsiukh State higher institution “I. Horbachevsky Ternopil State Medical University of the Ministry of Health of Ukraine” Summary Simulation of mechanical injuries of various localization in the early period traumatic disease leads to the accumulation in serum IL-6. After application of the skeletal injuries observed vibrational dynamics rate of increase in the first – after 1 day, reduced to the level control – 3 days and again, but smaller in amplitude – after 7 days. In the dynamics of cranial injury rate increases significantly in 7 days compared to the control. After applying the combined trauma of the content in serum blood IL-6 1 day after reaching the maximum level and remains at that level to 7 days. After 3-7 days in this group figure significantly higher than in other groups, where modeled separately and individually skeletal, cranialin juries, this effect manifested their mutual encumbrance. Key words: skeletal, cranial, cranioskeletal injury, interleukin-6, experiment.